(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
This article is a summary of the Anthropological Report of Historical, Economic, Environmental and Socio-Cultural Characterization elaborated in 2009 as an activity of the Basic Quilombola Environmental Program of the Transposition Project of the São Francisco River. The purpose of the report was to define the territory of the Community of Remnants of Quilombo de Santana, located in the municipality of Salgueiro – PE. The quilombola territory of Santana, in Salgueiro-PE, far from the headquarters of the municipality 22 kilometers is made up of 05 interlinked sites. Namely, they are: Santana, Jurema, Pottery, Recanto e Livramento. Approximately 66 families live in the territory. The present limits of the territory include the lands located between Umãs, Sites New, Boqueirão, Pau Ferro and Várzea do Ramo.